2017
DOI: 10.1055/s-0037-1603967
|View full text |Cite
|
Sign up to set email alerts
|

Survey on Aesthetic Vulvovaginal Procedures: What do Portuguese Doctors and Medical Students Think?

Abstract: Objective To assess the medical doctors and medical students' opinion regarding the evidence and ethical background of the performance of vulvovaginal aesthetic procedures (VVAPs Conclusions While medical doctors and students acknowledge the lack of evidence and scientific support for the performance of VVAPs, most do not raise ethical objections about them, especially if they are students or plastic surgeons, or if they have had or have considered having plastic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…12 Although medical students, young doctors, and gynecologists have more knowledge about VVAPs, all health professionals must know recent trends in VVA. 13,14 Regarding the ethical aspects of VVAPs, our results are consistent with the Royal College of Obstetrics and Gynecology. 15 This analysis recommends that ethical opinion for patients opting for female genital cosmetic procedures needs to be discussed carefully with microscopic details and should be opted only for indicated patients; for example, if sexual health is compromised physically (atrophy or laxity) and psychologically.…”
Section: Discussionsupporting
confidence: 88%
“…12 Although medical students, young doctors, and gynecologists have more knowledge about VVAPs, all health professionals must know recent trends in VVA. 13,14 Regarding the ethical aspects of VVAPs, our results are consistent with the Royal College of Obstetrics and Gynecology. 15 This analysis recommends that ethical opinion for patients opting for female genital cosmetic procedures needs to be discussed carefully with microscopic details and should be opted only for indicated patients; for example, if sexual health is compromised physically (atrophy or laxity) and psychologically.…”
Section: Discussionsupporting
confidence: 88%
“…Of note, even the use of LASER for hair removal has been related to serious urogynecologycal complications, such as labial adhesion with cryptomenorrhea, and acute urinary retention . In one survey, 85.9% of physicians stated that there is no medical indication for the performance of such procedures …”
Section: Other Possible Uses Of Laser (Vulvar Bleaching/whitening/brimentioning
confidence: 99%
“…128 In one survey, 85.9% of physicians stated that there is no medical indication for the performance of such procedures. 129 Labiaplasty is one of the most performed female cosmetic genital procedures worldwide. There are several techniques described, some with the use of LASER.…”
Section: Lichen Sclerosusmentioning
confidence: 99%
“…65 In a survey among medical doctors and students, 71.0% indicated that there is never or rarely an indication for those procedures (56.0% if only plastic surgeons were considered). 67 The separation between a clitoral and a vaginal (G-spot) orgasm seems to be reminiscence of the Freudian concepts − the pressure is the same: those who can only achieve it through "direct" clitoral stimulation are considered to be in a more immature sexual stage. 68 There is no evidence that vaginal and clitoral orgasms are different; pure vaginal stimulation during coitus probably does not happen.…”
Section: Discussionmentioning
confidence: 99%